Direct mapping of chemical oxidation of individual graphene sheets through dynamic force measurements at the nanoscale - Froning, Jens P; Lazar, Petr; Pykal, Martin; Li, Qiang; Dong, Mingdong; Zbořil, Radek; Otyepka, Michal (Nanoscale, 2017)
Graphene oxide is one of the most studied nanomaterials owing to its huge application potential in many fields, including biomedicine, sensing, drug delivery, optical and optoelectronic technologies. However, a detailed description of the chemical composition and the extent of oxidation in graphene oxide remains a key challenge affecting its applicability and further development of new applications. Here, we report direct monitoring of the chemical oxidation of an individual graphene flake during ultraviolet/ozone treatment through in situ atomic force microscopy based on dynamic force mapping. The results showed that graphene oxidation expanded from the graphene edges to the entire graphene surface. The interaction force mapping results correlated well with X-ray photoelectron spectroscopy data quantifying the degree of chemical oxidation. Density functional theory calculations confirmed the specific interaction forces measured between a silicon tip and graphene oxide. The developed methodology can be used as a simple protocol for evaluating the chemical functionalization of other two-dimensional materials with covalently attached functional groups.